(untitled) (Research, Society and Development, 2020)
Cases of HIV-infected women are increasing, particularly among those of reproductive age. In this context, the aim of this study is to analyze the prevalence and risk factors associated with HIV infection in pregnant women in the state of Piauí. This study is a cross-sectional epidemiological study with 873 pregnant women attended at Dona Evangelina Rosa Maternity (MDER), PI, conducted between January 2016 and December 2017. The research was developed through the collection of samples, epidemiological information and diagnosis of HIV infection in pregnant women. Data were organized using the Statistical Package for Social Sciences 20.0 (SPSS) statistical program. For comparative analysis, the chi-square test (c2) was used, establishing a significance level lower than 5% (p <0.05), with 95% confidence intervals (95% CI). From the analysis, it was concluded that the prevalence of pregnant women with HIV was 1.9%, mainly characterized as housewives aged 12 to 23 years, heterosexual, living with a partner, complete elementary school, urban residents , with their own house and family income of one to two minimum wages. Crossing HIV prevalence with behavioral variables associated with increased exposure to virus infection resulted in significant association only in the following variables: tattooing (p = 0.002), have you ever used illicit drugs (p = 0.000) and past or past use? current intravenous illicit drug (p = 0.000).